EFFECT OF MOLARITY AND SOLVENT ON THE OPTICAL PARAMETERS OF THE LIQUIDCRYSTALLINE POLYMER F8T2 AND SURFACE MORPHOLOGY PROPERTIES OF THE F8T2 FILM - Gündüz, Bayram (Muş Alparslan Üniversitesi, 2013)
In this study, we investigated the surface morphology of the liquid-crystalline polymer poly[(9, 9-dioctylfluorenyl-2, 7-diyl)-co-bithiophene] (F8T2) film by high performance atomic force microscopy and the surface roughness parameters of the F8T2 film such as; roughness average (sa), root mean square roughness (sq), surface skewness (ssk) and surface kurtosis (sku) value were obtained. Also, we reported the morphology of the cross-section (wall) and height histogtams of the F8T2 film by AFM. The positive skewness and high kurtosis of the F8T2 film are desirable to achieve low friction applications. The ratios of the sq to the sa for the F8T2 film were found to be 1.271 and 1.292. Then, we investigated in detail the optical properties of the solutions of the F8T2 polymer for different molarities and solvents. The absorbance, molar extinction coefficient (?) and mass extinction coefficient (?) values of the F8T2 polymer decrease with decreasing molarity. The average transmittance, absorption band edge, direct (Egd) and indirect (Egid) energy-gap values of refraction of the F8T2 polymer increase with decreasing molarity. The maximum absorption wavelength (?max) of the solutions of the F8T2 for 1.200 and 0.800 µM was found to be 455 nm, while the ?max of the F8T2 polymer for DCM, THF and Chloroform solvents were found to be 447, 453 and 455 nm, respectively. The yellow light of the F8T2 polymer is emitted 586 nm. The maximum mass extinction coefficient (?max) values at maximum molar extinction coefficient (?max) (2.246x106 and 1.736x106 Lmol-1cm-1, respectively) of the solutions of the F8T2 polymer for 1.200 and 0.800 µM were found to be 59.105 and 45.684 Lg-1cm-1, respectively, while the ?max values at ?max(2.461x106, 2.371x106 and 2.246x106 Lmol-1cm-1, respectively) of the F8T2 polymer for DCM, THF and Chloroform solvents were found to be 64.763, 62.395 and 59.105 Lg-1cm-1, respectively. The Egd values (2.413 and 2.387 eV, respectively) of the F8T2 polymer for 0.800 µM and Chloroform solvent are the highest values, while the Egd values (2.220 and 2.279 eV) of the F8T2 polymer for 19.737 µM and THF solvent are the lowest values. The Egid values (2.345 and 2.305 eV, respectively) of the F8T2 polymer for 0.800 µM and Chloroform solvent are the highest values, while the Egid values (2.113 and 2.053 eV) of the F8T2 polymer for 19.737 µM and THF solvent are the lowest values. The obtained Egid values of the F8T2 polymer are more lower than that of the obtained Egd values of the F8T2 polymer. Thus, the optical band-gap of the solution of the F8T2 polymer was decreased with increasing molarity and using THF solvent among DCM, THF and Chloroform solvents

Bu çalışmada, yüksek verimli atomik kuvvet mikroskobu ile sıvı-kristal polimeri olan poly[(9, 9-dioctylfluorenyl-2, 7-diyl)-co-bithiophene] (F8T2) filminin yüzey morfolojisini araştırdık ve F8T2 filminin pürüzlülük ortalaması (sa), kök-ortalama-kare sapması (sq), yüzey çarpıklığı (ssk) ve yüzek basıklığı (sku) değerleri gibi yüzey pürüzlülük parametrelerini elde ettik. Aynı zamanda, AFM ile F8T2 filminin kesiti (duvar) ve yükseklik histogramlarının morfolojisini de inceledik. F8T2 filminin pozitif çarpıklık ve yüksek basıklık değerleri, düşük sürtünme uygulamalarını sağlamak için istenilen bir durumdur. F8T2 filmi için sq’nun sa’ya oranları, 1.271 ve 1.292 olarak bulundu. Daha sonra, farklı molariteler ve çözücüler için, F8T2 polimerin solüsyonlarının optik özelliklerini detaylı bir şekilde araştırdık. F8T2 polimerinin absorbans, molar tükenme katsayısı (?) ve kütle tükenme katsayısı (?) değerleri, molaritenin azalmasıyla azalmaktadır. F8T2 polimerinin, ortalama geçirgenlik, absorbans bant kenarı, doğrudan (Egd) ve dolaylı (Egid) enerji bandı değerleri molaritenin azalmasıyla artmaktadır. DCM, THF ve kloroform çözücüleri için F8T2 polimerinin maksimum absorbans dalga boyu (?max) değerleri sırasıyla 447, 453 ve 455 nm olarak bulunurken, 1.200 ve 0.800 ?M için F8T2’nin solüsyonlarının ?max değeri 455 nm olarak bulundu. F8T2 polimerinin sarı ışığı, 586 nm’de yayıldı. DCM, THF ve kloroform çözücüleri için F8T2 polimerinin maksimum molar tükenme katsayısı (?max) değerlerindeki (sırasıyla 2.461x106, 2.371x106 ve 2.246x106 Lmol-1cm-1) maksimum kütle tükenme katsayısı (?max) değerleri, sırasıyla 64.763, 62.395 ve 59.105 Lg-1cm-1 olarak bulunurken, 1.200 ve 0.800 ?M için F8T2 polimer solüsyonlarının ?max değerlerindeki (sırasıyla 2.246x106 ve 1.736x106 Lmol-1cm-1) ?max değerleri, sırasıyla 59.105 ve 45.684 Lg-1cm-1 olarak bulundu. 19.737 ?M ve THF çözücüsü için F8T2 polimerinin Egd değerleri (sırasıyla 2.220 ve 2.279 eV) en düşük değerler iken, 0.800 ?M ve kloroform çözücüsü için F8T2 polimerinin Egd değerleri (sırasıyla 2.413 ve 2.387 eV) en yüksek değerlerdir. 19.737 ?M ve THF çözücüsü için F8T2 polimerinin Egid değerleri (sırasıyla 2.113 ve 2.053 eV) en düşük değerler iken, 0.800 ?M ve kloroform çözücüsü için F8T2 polimerinin Egid değerleri (sırasıyla 2.345 ve 2.305 eV) en yüksek değerlerdir. F8T2 polimerinin elde edilen Egid değerleri, F8T2 polimerinin elde edilen Egd değerlerinden çok daha düşüktür. Sonuç olarak, F8T2 polimer solüsyonlarının optik band-aralığı, molaritenin artmasıyla ve DCM, THF ve kloroform çözücüleri arasında THF kullanılarak azalabileceği görüldü.
msufbd
Keywords: surface roughness parameters; F8T2; molar/mass extinction coefficient; molarity; optical band gap; optical parameters